NON-HLA MARKERS OF TRANSPLANT REJECTION - GJERTSON DAVID W; BUTLER CARRIE L; REED ELAINE F; HICKEY MICHELLE (2021)
The present invention generally relates to transplantation rejection. In particular, the present invention provides compositions, kits, assays, and methods of determining if a subject has allograft rejection, or an increased risk of developing rejection after transplantation, and methods of treatment thereof. 本发明总体上涉及移植排斥。特别地，本发明提供了确定受试者是否具有同种异体移植物排斥或增加的移植后发展出排斥的风险的组合物、试剂盒、测定和方法，以及其治疗方法。